Preclinical animal study and human clinical trial data of co-electrospun poly(L-lactide-co-caprolactone) and fibrinogen mesh for anterior pelvic floor reconstruction - Wu XJ (Dove Medical Press, 2016)
Xujun Wu,1,2,* Yuru Wang,3,* Cancan Zhu,2 Xiaowen Tong,3 Ming Yang,2 Li Yang,2 Zhang Liu,1,2 Weihong Huang,2 Feng Wu,2 Honghai Zong,2 Huaifang Li,3 Hongbing He2,41School of Materials Science and Engineering, Shanghai Jiao Tong University, 2Shanghai Pine & Power Biotech Co. Ltd., 3Department of Obstetrics and Gynecology, Shanghai Tongji Hospital, Tongji University, 4Section of Tissue Engineering, Institute of Peripheral Vascular Surgery, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workAbstract: Synthetic and biological materials are commonly used for pelvic floor reconstruction. In this study, host tissue response and biomechanical properties of mesh fabricated from co-electrospun poly(L-lactide-co-caprolactone) (PLCL) and fibrinogen (Fg) were compared with those of polypropylene mesh (PPM) in a canine abdominal defect model. Macroscopic, microscopic, histological, and biomechanical evaluations were performed over a 24-week period. The results showed that PLCL/Fg mesh had similar host tissue responses but better initial vascularization and graft site tissue organization than PPM. The efficacy of the PLCL/Fg mesh was further examined in human pelvic floor reconstruction. Operation time, intraoperative blood loss, and pelvic organ prolapse quantification during 6-month follow-up were compared for patients receiving PLCL/Fg mesh versus PPM. According to the pelvic organ prolapse quantification scores, the anterior vaginal wall 3 cm proximal to the hymen point (Aa point), most distal edge of the cervix or vaginal cuff scar point (C point), and posterior fornix point (D point) showed significant improvement (P<0.01) at 1, 3, and 6 months for both groups compared with preoperatively. At 6 months, improvements at the Aa point in the PLCL/Fg group were significantly more (P<0.005) than the PPM group, indicating that, while both materials improve the patient symptoms, PLCL/Fg mesh resulted in more obvious improvement.Keywords: anterior pelvic floor reconstruction, polypropylene mesh, poly(L-lactide-co-caprolactone), fibrinogen, pelvic organ prolapse quantification